AN ANALYSIS OF TEXTUAL MEANING ON STUDENTS’ WRITING OF RECOUNT TEXTS - Febriyana, Anggie; Sofwan, Ahmad; Farida, Alief Noor (ELT Forum: Journal of English Language Teaching, 2018)
The topic of this study is the textual meaning on students‟ recount texts of the 4thsemester students of English Department, Semarang State University in theAcademic Year 2016/2017. The analyses intend to figure out what Thematicstructures are displayed and what Thematic progressions are employed in thestudents‟ recount texts. The approach used in this study is qualitative descriptivemethod, and some quantitative approaches to enhance the depth of results. Theunits of analysis of this study were clauses in the 4th semester students‟ recount textstaken from Genre-Based Writing course. The results of the Thematic structuresanalysis show that unmarked topical Theme is the most frequently used rather thanthe marked one. Modal adjunct is the only constituent of interpersonal Theme thatis found to show the writer‟s judgment. Moreover, structural and conjunctiveadjunct are used in relating the clause to its context or another clause. In addition,there only one continuative found in the text to signal a new move is made. Thestudy also shows that the students used re-iteration (constant) to make the text keepfocused. Then, zigzag pattern is commonly used in relative clauses which replacesubject. While multiple (split) pattern is used to introduce a number of differentpieces of information which is made as Theme in subsequent clauses.